Telecommuting Travel Behavior: Examining the Influence of Work Status on Distance and Mode Choice in the National Capital Region - Garden, Benjamin W.C. (My University, 2012)
This study explores telecommuter travel behaviour by examining discretionary travel distance and mode choice. The study utilizes data obtained from the 2005 origin-destination survey conducted by TRANS, a joint transportation planning committee serving the National Capital Region of Canada. The study compares and explains the discretionary travel behavior of teleworkers relative to other population groups and identifies that the average teleworker travels 3 times farther than regular workers and 1.7 times farther than non-workers for discretionary purposes. Regression indicates that dependent children, vehicle accessibility, housing type, residential distance to the urban core, land-use mix, residence within a Greenbelt region and day of the week all positively affect travel distance. Conversely, age, proximity to shopping centers and inclement weather demonstrate significant negative effects. Then, through binary logistic regression, the study confirms that work status significantly influences mode choice. Similarly, the following predictor variables demonstrate a significant positive effect towards active mode choice: teleworker work status, larger household size, greater income, warmer temperature, closer proximity to shopping centers, apartment housing type, trips for recreational and restaurant purposes, taking subsequent trips in a day, and travel between 8:00 A.M. and 4:00 P.M. On the contrary, increased entropy, trips within the Greenbelt region, dependent children under 16 years old, increased vehicle accessibility and trips for transporting someone or for shopping purposes all reduce the probability of active travel mode choice.
Keywords: Travel Behaviour; telework; telecommute; impact; TDM; travel demand management; transportation demand management; travel distance; mode choice; Geographic Information Sciences; Human Geography; Other Geography; Geographic Information Sciences